An Unimaginable Start of Indo-Pak relations in the Postwar Era - Kumar, Dr. Manoj (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
This paper precisely describe the conflict and way of resolution in between India and Pakistan, still in hope that one day we all will establish a profound and secure relation with our nabour country Pakistan as their own citizen also wishes the same. This paper gives a brief idea about the all the initiative held by India in order to minimize the conflict and their consequences. Key words: Lahore, Bajpayee, Constitution, indo-Pak Border.